RESPONSIBILITY FOR SPACE ACTIVITIES ACCORDING TO INTERNATIONAL LAW - Agit Yogi Subandi (PRANATA HUKUM, 2021)
Space law, described as a "body of law" that regulates activities related to space. As with international law in general, space law uses legal bases, among others, a.l; international treaties, conventions, and resolutions issued by the general assembly of the United Nations to regulate these activities. Because this space activity carries a very large risk, such as failing to orbit the space vehicle at its orbital point, causing damage to the vicinity of the launch site. Based on that, what needs to be discussed in this paper is what is the concept of responsibility in space activities? And what is the definition of liability under international law? The existence of arrangements regarding this activity, it is shown that the responsibility is public and accountability is in the form of compensation.